The RasGAP Proteins Ira2 and Neurofibromin Are Negatively Regulated by Gpb1 in Yeast and ETEA in Humans - Phan, Vernon T. (American Society for Microbiology (ASM), 2010)
The neurofibromatosis type 1 (NF1) gene encodes the GTPase-activating protein (GAP) neurofibromin, which negatively regulates Ras activity. The yeast Saccharomyces cerevisiae has two neurofibromin homologs, Ira1 and Ira2. To understand how these proteins are regulated, we utilized an unbiased proteomics approach to identify Ira2 and neurofibromin binding partners. We demonstrate that the Gpb1/Krh2 protein binds and negatively regulates Ira2 by promoting its ubiquitin-dependent proteolysis. We extended our findings to show that in mammalian cells, the ETEA/UBXD8 protein directly interacts with and negatively regulates neurofibromin. ETEA contains both UBA and UBX domains. Overexpression of ETEA downregulates neurofibromin in human cells. Purified ETEA, but not a mutant of ETEA that lacks the UBX domain, ubiquitinates the neurofibromin GAP-related domain in vitro. Silencing of ETEA expression increases neurofibromin levels and downregulates Ras activity. These findings provide evidence for conserved ubiquitination pathways regulating the RasGAP proteins Ira2 (in yeast) and neurofibromin (in humans).